2013
DOI: 10.1007/s00438-013-0743-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis distinguishes tissue-specific and gender-related functions among adult Ascaris suum tissues

Abstract: Over a billion people are infected by Ascaris spp. intestinal parasites. To clarify functional differences among tissues of adult A. suum, we compared gene expression by various tissues of these worms by expression microarray methods.. The A. suum genome was sequenced and assembled to allow generation of microarray elements. Expression of over 40,000 60-mer elements was investigated in a variety of tissues from both male and female adult worms. Nearly 50 percent of the elements for which signal was detected ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 66 publications
4
20
2
Order By: Relevance
“…This term was identified as being enriched in the head of A. suum in the previous microarray study [16], and was enriched only in the head-overexpressed genes in this study, which could be expected since most of the other internal tissues are not cuticle-lined, or are only partially lined with cuticle (e.g. pharynx or the distal posterior part of the intestine-anus).…”
Section: Resultssupporting
confidence: 60%
“…This term was identified as being enriched in the head of A. suum in the previous microarray study [16], and was enriched only in the head-overexpressed genes in this study, which could be expected since most of the other internal tissues are not cuticle-lined, or are only partially lined with cuticle (e.g. pharynx or the distal posterior part of the intestine-anus).…”
Section: Resultssupporting
confidence: 60%
“…Tissue transcriptional studies of some important genes have been reported in A. suum, H. contortus and B. malayi, which have provided valuable information regarding tissue-specific genes (Yin et al, 2008;Wang et al, 2013;Rosa et al, 2014). For example, Bm-shp-1 expression in the epithelium of uterine and Bm-msp-1 in spermatocytes and spermatids indicated potential roles in reproductive processes (Jiang et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Recent molecular investigations have provided invaluable data of gender-specific or -enriched genes in development and reproductive processes that could be potential targets to disrupt development or reproduction of parasites (Nisbet and Gasser, 2004;Nisbet et al, 2008;Li et al, 2011;Wang et al, 2013). Specifically, the functional roles of the male-specific serine/threonine protein phosphatase 1 (PP1) gene (stp-1) in reproduction have been investigated in Oesophagostomum dentatum (Boag et al, 2000;Boag et al, 2003), Trichostrongylus vitrinus, Haemonchus contortus and T. canis (Hu et al, 2007;Campbell et al, 2010;Ma et al, 2014), indicating potential roles of stp-1 in spermatogenesis of nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…A previous gene expression study in A. suum (14) found that the intestine expressed many more gender-specific genes (and had many more gender-specific functions) than other somatic tissues tested; (2) NHR-25, which is expressed in the C. elegans intestine and regulates an endocrine signaling cascade that ultimately modulates dietary fat uptake and de novo fat synthesis (83); (3) CEH-30, an anti-apoptotic gene regulating sexual identity and is transcriptionally repressed by TRA-1 in C. elegans (84) (the TF for the most significantly enriched motif in the intestinal tissue); (4) ELT-1, and (5) ELT-3, which are functionally redundant GATA transcription factors responsible for early intestine development in C. elegans (85), but only ELT-3 has been implicated in controlling the expression of age-related genes in the intestine (86).…”
Section: Functional Enrichment Analyses Reveal Known and Novel Functimentioning
confidence: 99%
“…However, the parasitic roundworm Ascaris suum (size 15-40 cm; which also has a complete draft genome available (12,13)) is large enough that the intestine can be physically manipulated for this purpose. The large size of the A. suum intestine has also supported the broad molecular characterization of intestinal cell functions based on gene expression studies using expressed sequence tags (3), microarray (14) and RNA-seq approaches (15). These studies analyzed the transcript expression level in whole intestinal tissue relative to other tissues but not protein expression or compartmentalization of proteins within intestinal tissue, although a proteomic study of A. suum proteins in nonintestinal fluids including perienteric and uterine fluids was recently reported (16).…”
mentioning
confidence: 99%